New Treatment of Vertigo Caused by Jugular Bulb Abnormalities. (August 2014) - Hitier, Martin; Barbier, Charlotte; Marie- Aude, Thenint; Moreau, Sylvain; Courtheoux, Patrick; Patron, Vincent
Objective . Jugular bulb abnormalities can induce tinnitus, hearing loss, or vertigo. Vertigo can be very disabling and may need surgical treatments with risk of hearing loss, major bleeding or facial palsy. Hence, we have developed a new treatment for vertigo caused by jugular bulb anomalies, using an endovascular technique. Patients . Three patients presented with severe vertigos mostly induced by high venous pressure. One patient showed downbeat vertical nystagmus during the Valsalva maneuver. The temporal-bone computed tomography scan showed a high rising jugular bulb or a jugular bulb diverticulum with dehiscence and compression of the vestibular aqueduct in all cases. Intervention . We plugged the upper part of the bulb with coils, and we used a stent to maintain the coils and preserving the venous permeability. Results . After 12- to 24-month follow-up, those patients experienced no more vertigo, allowing return to work. The 3-month arteriographs showed good permeability of the sigmoid sinus and jugular bulb through the stent, with complete obstruction of the upper part of the bulb in all cases. Conclusion . Disabling vertigo induced by jugular bulb abnormalities can be effectively treated by an endovascular technique. This technique is minimally invasive with a probable greater benefit/risk ratio compare with surgery.